The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1080/09540121.2011.630345
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life among Brazilian women living with HIV/AIDS

Abstract: The purpose of the present study was to assess quality of life (QoL) in Brazilian women living with HIV/AIDS, according to the World Health Organization Quality of Life HIV-BREF (WHOQoL-HIV-BREF) domains. A quantitative-based, cross-sectional, analytical study was carried out in healthcare centers specialized in assisting people living with HIV/AIDS, located in a municipality of the state of São Paulo, Brazil. One hundred and six women of age 18 years or more, users of the public healthcare system, participate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 31 publications
1
19
0
5
Order By: Relevance
“…(10) According to the quality of life domains, the individuals presented good scores in most domains, thereby emphasizing the Psychological (67.9) and Spirituality, religion and personal beliefs (65.7) domains, and worst average scores in the Environment (59.2) and Level of independence (55.1) domains. In Brazilian (3,6) and international (10,11) studies, the Environment and Level of independence domains also had lower scores compared to other quality of life domains.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(10) According to the quality of life domains, the individuals presented good scores in most domains, thereby emphasizing the Psychological (67.9) and Spirituality, religion and personal beliefs (65.7) domains, and worst average scores in the Environment (59.2) and Level of independence (55.1) domains. In Brazilian (3,6) and international (10,11) studies, the Environment and Level of independence domains also had lower scores compared to other quality of life domains.…”
Section: Discussionmentioning
confidence: 99%
“…Thereby, higher scores were identified among those who have In other research in the area, employment or retirement, income above one minimum wage, and higher levels of education were associated with higher quality of life scores. (3) A study evaluating employability and adherence to antiretroviral therapy showed that employed people were 27% more likely to adhere to antiretroviral therapy than unemployed people. (12) Considering the influence of the use of antiretrovirals, most of the sample had problems with treatment adherence regarding the scheme, doses and schedules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results are seen in Latin American countries, which occupy the 4th place in number of cases; while the Western Europe and North American countries are in the last position. Therefore, this overview is related to the social and economic situation of these populations, since the Latin American countries are considered underprivileged (39) . According to an epidemiological survey of the State Secretariat of Health of Alagoas, in 2012, the municipalities: Coqueiro Seco, Flexeiras and Joaquim Gomes showed higher rates of pregnant women with HIV/AIDS than the capital city Maceió (40) .…”
Section: Discussionmentioning
confidence: 99%
“…QOL assessment for PLHA on ART is important for monitoring the disease's impact and infection progression (Reis, Santos, & Gir, 2012). According to the World Health Organization (WHO), QOL should be evaluated in terms of an individual's culture and value systems (The WHO-QOL Group, 1998).…”
Section: Introductionmentioning
confidence: 99%